2016
DOI: 10.2196/resprot.4094
|View full text |Cite|
|
Sign up to set email alerts
|

Can Internet-Based Sexual Health Services Increase Diagnoses of Sexually Transmitted Infections (STI)? Protocol for a Randomized Evaluation of an Internet-Based STI Testing and Results Service

Abstract: BackgroundEnsuring rapid access to high quality sexual health services is a key public health objective, both in the United Kingdom and internationally. Internet-based testing services for sexually transmitted infections (STIs) are considered to be a promising way to achieve this goal. This study will evaluate a nascent online STI testing and results service in South East London, delivered alongside standard face-to-face STI testing services.ObjectiveThe aim of this study is to establish whether an online test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…We and other researchers have used text messages and social media to encourage high-risk groups to use existing and novel internet-based services. 16,54 In this research we have demonstrated that content delivered by IT targeting safer sex can be developed so that it is acceptable to young people. A range of social media and mobile IT could also be used to encourage high-risk people who are not currently service users to adopt safer sexual practices.…”
Section: Potential Implications For Other Similar Interventionsmentioning
confidence: 90%
“…We and other researchers have used text messages and social media to encourage high-risk groups to use existing and novel internet-based services. 16,54 In this research we have demonstrated that content delivered by IT targeting safer sex can be developed so that it is acceptable to young people. A range of social media and mobile IT could also be used to encourage high-risk people who are not currently service users to adopt safer sexual practices.…”
Section: Potential Implications For Other Similar Interventionsmentioning
confidence: 90%
“…Ethical approval was obtained from the National Research Ethics Service (NRES) Committee London–Camberwell St Giles (Ref 14/LO/1477). The trial protocol was accepted for publication in April 2015 and was published in January 2016 [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The trial steering committee approved the pre-specified statistical analysis plan prior to unblinding. Our study was powered for our co-primary outcome of the proportion of participants diagnosed with an STI in each group [ 27 , 28 ]. Two factors determined the number of participants needed: the estimated proportion of participants with an STI and the size of the treatment effect.…”
Section: Methodsmentioning
confidence: 99%
“…In the field of sexual health, Web-based testing services are widely considered to overcome barriers faced by individuals seeking testing for sexually transmitted and blood-borne infections (STBBIs) [1]. By offering an opportunity to test at a local laboratory or at home without needing to see a provider or present to a clinic, these services may eliminate known barriers related to conventional testing services (although to date this has not been well studied).…”
Section: Introductionmentioning
confidence: 99%